Zuriah - Institut Agama Islam Negeri Curup (Institut Agama Islam Negeri (IAIN) Curup, 2020)
All aspects of early childhood education.
Keywords: Early childhood education : Indonesia : Periodicals; Early childhood education : Periodicals; Early childhood education; Indonesia